Social Responsibility On Purchase Intention Based On Customer Company Identification - Zain, Lauda Radhea; Marsasi, Endy Gunanto (Catholic University Musi Charitas, 2023)
Social responsibility is achieving goals for the community, one of which is purchase intention, which is influenced by customer company identification, trust, general attitude, and purchase intention based on the sustainability theory on marketing, especially when companies maintain their status and standing in the business world. This study aims to determine the effect of the relationship between hypotheses on bottled mineral water products from the research gap. The object research focused on bottled mineral water product companies with the subject of bottled mineral water consumers from all walks of life. This research used Structural Equation Modeling (SEM) with 232 respondents who participated in responding to the research questionnaires. The results of the study indicate the rejection of one hypothesis that connects the influence between trust and purchase intention on bottled mineral water products due to privacy issues among consumers.